Evaluation of Extensor Pollicis Brevis as a Recipient of Tendon Transfer for Thumb Extension - Bhardwaj, Praveen; Muddappa, Poonacha Puchimada; Bindesh, Dadi; Sabapathy, Shanmuganathan Raja (Indian Journal of Plastic Surgery, 2019)
Introduction Rerouting of the extensor pollicis longus (EPL) is the standard part of tendon transfer surgery for thumb extension. It is done to overcome the ulnar vector of the EPL action. Extensor pollicis brevis (EPB), however, produces better thumb abduction and extension by virtue of its radial vector. The described anatomical variation of EPB extending the thumb interphalangeal joint (IPJ), therefore, gives the “best combination” of movements by a single-thumb extensor tendon.Materials and Methods We performed this transfer in six patients in whom the EPB was found to be extending the IPJ while checked intraoperatively. Three of these six patients were cases of radial nerve palsy and the other three presented with brachial plexus palsy. The outcome was assessed by measuring palmar and radial abduction of the thumb, Kapandji’s score, and Bincaz’s scale.Results We found satisfactory results in all the six patients. In our series, patients had an average radial extension of the thumb of 29.2 degrees and an average palmar abduction of the thumb of 65.7 degrees. On evaluation with the Bincaz score; one patient had excellent result, three patients had good results, and two patients had fair results.Conclusion In situations where EPL rerouting is not possible (as in cases where the donor tendon needs to reach the thumb from the ulnar side, for example, flexor carpi ulnaris), transfer to the EPB, provided it is extending the thumb IPJ, would produce better extension and abduction of the thumb than the transfer to the EPL.
Keywords: brachial plexus; radial nerve palsy; rerouting; tendon transfer; thumb extension; wrist drop; wrist extension